The identity of Coronella violacea Cantor, 1839, a senior synonym of Oligodon kheriensis Acharji & Ray, 1936 (Squamata: Colubridae) - Lee, Justin L. (Zootaxa, 2026)
Theodore Cantor described Coronella violacea in 1839 for a colubrid snake collected from “Rungpore” (now Rangpur, Bangladesh). It was applied to several species in the genus Oligodon until Smith (1940) treated the name as a junior synonym of Oligodon cyclurus (Cantor, 1839). Evidence from the unpublished notes and watercolor drawings of Cantor indicate Coronella violacea is not a synonym of O. cyclurus, but is conspecific with Oligodon kheriensis Acharji & Ray, 1936. The collector of the holotype of Coronella violacea is identified as Honoratus Bonnevie, a Norwegian-born merchant and indigo plantation owner who lived in Rangpur during Cantor’s residency in British India. Precedence cannot be reversed in favor of O. kheriensis, so the older name is resurrected as Oligodon violaceus stat. reinstat., with O. kheriensis relegated as a junior synonym. Since the holotype of Coronella violacea is considered lost, the holotype of Oligodon kheriensis is designated as the neotype, an act that objectively links the two nomina with one another.